Incidence, risk factors and predictors of cardiovascular mortality for aortic stenosis among patients with diabetes mellitus. (September 2022) - Ko, Tsung-Yu; Lin, Ting-Tse; Hsu, Jung Chi; Yang, Yen-Yun; Chuang, Shu-Lin; Lin, Lian-Yu; Kao, Hsien-Li; Ho, Yi-Lwun
Highlights: Age, female, chronic kidney disease, hyperlipidemia, and peripheral arterial disease increase the risk of aortic stenosis in patients with type 2 diabetes. Aortic stenosis increases the risk of hospitalization for heart failure and cardiovascular mortality in patients with type 2 diabetes. Severity of aortic stenosis (moderate/severe), body mass index (<27 kg/m 2 ), hypertension, hyperuricemia, left ventricular dysfunction (ejection fraction < 50%), and hematocrit (<38%) are associated with increased cardiovascular mortality in patients with type 2 diabetes and aortic stenosis. Abstract: Aims: To find the incidence, risk factors and predictors of cardiovascular (CV) mortality for aortic stenosis (AS) in patients with type 2 diabetes mellitus (T2DM). Methods: Between 2014 and 2019, 20, 979 patients with T2DM who underwent echocardiography were enrolled for analysis. The mean follow-up period was 34 months. Multiple risk factors and outcomes for patients with and without AS were presented. Results: AS was present in 776 (3.70%) patients. Age, female, chronic kidney disease, hyperlipidemia, and peripheral arterial disease statistically increased risk of AS. The CV mortality (adjusted hazard ratio [aHR] = 1.97; 95% confidence interval [CI] 1.336 – 2.906, p < 0.001) and risk of hospitalization for heart failure (HHF) (aHR = 1.73, 95% CI 1.442–2.082, p < 0.001) were significantly increased in patients with AS, without significant differences in acute myocardial infarction and stroke. Severity of AS, body mass index (<27 kg/m 2 ), hypertension, hyperuricemia, left ventricular dysfunction (ejection fraction < 50%), and hematocrit (<38%) were significantly associated with increased CV mortality and HHF. Conclusions: AS was associated with an increased risk of CV mortality and HHF in patients with T2DM.